Challenges Affecting Health Referral Systems in Low-And Middle-Income Countries: A Systematic Literature Review - Nakayuki, Mildred; Basaza, Annabella; Namatovu, Hasifah (European Journal of Health Sciences, 2021)
Aims: Low and middle-income countries are still facing challenges of dysfunctional referral systems which have impaired health service provision. This review aimed at investigating these challenges to understand their nature, cause, and the impacts they have on health service provision. Methods: Database search was made in Google scholar, ACM Library, PubMed health, and BMC public health, and a total of 123 papers were generated. Only 14 fitted the inclusion criteria. Inclusion criteria included studies that were both quantitative and qualitative addressing challenges facing referral systems or health referral systems, studies describing the barriers to effective referral systems, and studies describing factors that affect referral systems. The review only included studies conducted in LMICs and included literature between January 2010 and February 2021. Findings: Results revealed that human resource and financial constraints, non-compliance, and communication are the key challenges affecting referral systems in LMICs. Recommendation: Countries that are facing these challenges need to overhaul the system and improve end-to-end communication between hospitals, improve capacity specifically in referral and emergency units, and sensitizing patients on the adherence to emergency protocols.